Cysticercus cellulosae Regulates T-Cell Responses and Interacts With the Host Immune System by Excreting and Secreting Antigens - Fan, Xianmin; Zhang, Yue; Ouyang, Renhui; Luo, Bo; Li, Lizhu; He, Wei; Liu, Meichen; Jiang, Nan; Yang, Fengjiao; Wang, Lingjun; Zhou, Biying (Frontiers in Cellular and Infection Microbiology, 2021)
Cysticercus cellulosae (C. cellulosae) excretes and secretes antigens during the parasitic process to regulate the host immune response; however, resulting immune response and cytokine production in the host during infection still remains unclear. We used C. cellulosae crude antigens (CAs) as controls to explore the effect of excretory secretory antigens (ESAs) on T-cell immune responses in piglets. C. cellulosae ESAs induced imbalanced CD4+/CD8+ T-cell proportions, increased the CD4+Foxp3+ and CD8+Foxp3+ T-cell frequencies, and induced lymphocytes to produce interleukin-10, which was mainly attributed to CD4+ and CD4−CD8− T cells. The ESAs also induced Th2-type immune responses. The results showed that the ability of C. cellulosae to escape the host immune attacks and establish a persistent infection may be related to host immune response regulation by the ESAs.